Czym jest edukacja biologiczna w wychowaniu człowieka? - Ilona Żeber-Dzikowska (Studia Ecologiae et Bioethicae)
Schools allow to develop and extend the approaches and attitudes in the social, moral, ideological, and religious spheres. The realization of these matters is possible due to the fulfillment of three basic school functions, i.e. didactic, educational, and protective. No one should forget that human education starts already in the period of childhood. Initially, parents introduce the children to the indispensable problems and matters in their future lives. It takes place in the form of games. They satisfy their growing need of gaining the knowledge, by answering numerous questions. They develop the knowledge through practical activities to let them gain experience, that is, organize walks, educational games, and so forth. Then young people begin school education, which influences, to a large degree, their lives. Then, in the educational process, the subject of Biology appears, almost certainly already known thanks to the parents’ education. The scientific discipline called Biology is a very important element in the education of people, which is helpful in understanding their own personalities and the surrounding reality. The wide range of biological contents as well as the short reflection on the subject of gaining the knowledge in the range of Biology allows us to notice, that this discipline, similarly to other disciplines shapes the personality of young, growing up people. All things considered, however, it differs from disciplines such as history, or mathematics, because it is closely and directly related to the human being and functioning, as the basis of human life. Biology, more considerably and effectively, than different disciplines, makes the students sensible towards human needs as well as the needs of nature and its protection.